Keputusan Pedagang Menabung di Koperasi Simpan Pinjam Syariah (KSPS) Baitul Maal Wat Tamwil (BMT) Sidogiri Cabang Silo (Studi Kasus Pasar Sempolan Kecamatan Silo Kabupaten Jember) - aria bagaskara, mohammad egar; Titisari, Purnamie; Munir, Akhmad (UPT Penerbitan Universitas Jember, 2024)
The aim of this research is to explore the decisions of traders to save at the Sharia Savings and Loans Cooperative (KSPS) Baitul Maal Wat Tamwil (BMT) Sidogiri Silo Branch (Case Study of Sempolan Market, Silo District, Jember Regency). This research is a type of descriptive qualitative research. Using participant observation methods, interview methods and documentation. The research results show that decision making at BMT Sidogiri is influenced by Islamic principles such as the absence of ribawi elements which are considered as the basis for saving decisions. For affordable locations along highways or cities, it will be easy for customers to find them to save. Speed and accuracy of service carried out in a friendly, fair, fast, precise and ethical manner so as to meet customer needs and satisfaction. For traders, the pick-up system is very important because it allows consumers to pay quickly and easily, making this system more valuable and different from other systems.